Grape Seed and Skin Extract Mitigates High Dosage Garlic-Induced Oxidative Stress in Rat Heart - Limam, Nadia; Marzouki, Lamjed; Amri, Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Garlic is a commonly used spice in folk medicine which could exert adverse health effects when given at high dose. Grape seed and skin extract (GSSE) exhibits a variety of beneficial effects even at high dose. In the present study we evaluated the toxicity of high garlic dose treatment on heart and the protective effect of GSSE. Rats were intraperitoneally (IP) administered either with garlic extract (5 g/kg bw) or GSSE (500 mg/kg bw) or a combination of garlic and GSSE at the same doses daily for one month. Data showed that high garlic dose induced heart toxicity and a pro-oxidative status characterized by increased MDA, NO, carbonyl protein, LDH, H2O2, free iron, and calcium. Unexpectedly garlic increased catalase and peroxidase but had no effect on superoxide dismutase. GSSE alone or in co-treatment with garlic had an opposite role and counteracted almost all garlic-induced deleterious effects to near control level. In conclusion, high garlic dose induced a pro-oxidative state into heart via the Fenton reaction between H2O2 and free iron, and GSSE exerted antioxidant properties.